384 ROLE OF C-JUN NH2-TERMINAL KINASE SIGNALING IN MALE GERM CELL APOPTOSIS IN MONKEYS AFTER MILD TESTICULAR HYPERTHERMIA AND/OR INTRATESTICULAR TESTOSTERONE DEPRIVATION. Issue 1 (1st January 2007) - Jia, Y.; Sinha Hikim, A. P.; Swerdloff, R. S.; Lue, Y. H.; Johnson, C.; Chiang, N.; Han, X.; Zhang, X. S.; Hu, Z. Y.; Li, Y. C.; Liu, Y. X.; Wang, C.
Abstract : Objective: In earlier studies, we have shown the involvement of the mitochondria-dependent intrinsic pathway for induction of male germ cell apoptosis in monkeys after transient testicular warming or administration of exogenous testosterone. The JNK (c-Jun NH2 -terminal kinase) signaling pathway has been implicated in the activation of apoptosis in various cell systems by stimulating the intrinsic pathway, but its role in testicular germ cell death is unclear. The goal of this study was to define the role of JNK in male germ cell apoptosis in monkeys after mild testicular hyperthermia or deprivation of intratesticular T or the combination of both interventions. Study Design: Groups of eight adult cynomolgus monkeys received one of the following treatments: (1) two empty Silastic implants (C); (2) two 5.5 cm T-implants (T); (3) daily exposure of testes to heat (43°C for 30 minutes) for 2 consecutive days (H); and (4) two T-implants plus exposure of the testes to heat for 2 consecutive days (T + H). Testicular biopsies were performed before and at 3, 8, and 28 days during treatment. Results: Activation of JNK, as evidenced by increase in phospho-c-Jun in testis lysates, was detected in all treatment groups on day 3. Compared with controls, where no staining was detected, a strong phospho-c-Jun staining was detected in the nuclei of apoptotic germ cells in all treatment groups and in the Sertoli cell nuclei at day 8 in H and H + T groups. To further define the role of JNK in apoptotic signal transduction, we examined the expression of JNK1, JNK2, and JNK3 in testes after these interventions. In the control testes, the expression of JNKs was localized in the Sertoli cell cytoplasm. Costaining for JNK2 and -3 and for TUNEL shows expression of both of these isoforms only in those germ cells undergoing apoptosis when compared with controls where these proteins were detected in cytoplasm. In contrast, JNK1 was detected in the Sertoli cell nuclei at day 8 in H and H + T groups. Conclusion: Our results indicate that (1) the JNK pathway may play a role in male germ cell apoptosis in monkeys; (2) JNK isoforms could have preferential effects on testis function; and (3) Sertoli cells participate in germ cell apoptosis triggered by heat stress via JNK signaling.